Decreasing the Intensity of Back Pain by Doing Maryam Gymnastics in Third Trimester Pregnant Women at Independent Midwife Practice Mrs.R - Oktaf, Celine; Bachri, Syaiful (D'Nursing and Health Journal (DNHJ), 2024)
ABSTRACT Background: Back pain is pain that occurs in the lumbosacral area. Low back pain will usually increase in intensity as the gestational age increases because this pain is the result of a shift in the woman's center of gravity and her posture so that efforts are needed to do maryam gymnastics activities. Maryam gymnastics is carried out in an effort to optimize the harmonization between the body modified by the movement of prayer movements so as to provide side effects of relaxation and promote emotional health, improve balance and body coordination. The aim is to analyze the decrease in back pain intensity through maryam gymnastics in third trimester pregnant women at Independent Midwife Practice Mrs. R. Method: The research design used One Group Pretest-Postest. The population was 33 third trimester pregnant women with a sample of 31. Sampling was done by simple random sampling. Observation sheet measuring instrument, with Wilcoxon test. Result: This study shows that most of the third trimester pregnant women experienced severe pain intensity before doing maryam gymnastics as many as 17 or 54.8%.Almost half of the third trimester pregnant women after doing maryam gymnastics experienced moderate pain intensity as many as 15 or 48.4%.Statistical test results there is a decrease in the intensity of back pain through maryam gymnastics in third trimester pregnant women at Independent Midwife Practice Mrs. R Jember Regency in 2023 with a p-value of 0.000 <α 0.05. Conclusion: The more routine the maryam gymnastics performed for 2 times a week with a duration of 10-15 minutes, the lower the intensity of back pain in pregnant women. It is recommended for pregnant women to further increase their sense of concern for the health of themselves and the fetus in order to better understand the importance of pregnant gymnastics activities in increasing the decrease in the intensity of back pain in Trimester III pregnant women.